Detection of Fusarium solani using cutinase antibody and its application in diagnosing fungal keratitis in an animal model - Hye-Jeong Jo; Min-Jeong Kim; Hae-Ahm Lee; Fu-Shi Quan; Hyun-Hee Kong; Eun-Kyung Moon (PLoS ONE, 2025)
Fungal keratitis (FK) is a sight-threatening infectious disease that can result in blindness if not appropriately treated. Although keratitis associated with filamentous fungi was rarely reported in the past, the incidence of fungal keratitis due to contact lens usage has increased. The clinical manifestations of fungal keratitis often resemble those of other corneal infections, potentially delaying accurate diagnosis and treatment. In this study, we developed a Fusarium-specific polyclonal peptide antibody targeting the cutinase of F. solani and evaluated its diagnostic potential for FK in an animal model. To assess the specificity of the cutinase antibody, we employed enzyme-linked immunosorbent assay (ELISA). The ELISA results demonstrated that the cutinase antibody specifically interacted with the cell lysates and conditioned media of F. solani. Additionally, an immunocytochemistry assay confirmed the specificity of the cutinase antibody for F. solani in samples co-cultured with human corneal epithelial (HCE) cells and other keratitis-causing agents. To validate our in vitro findings, FK animal models were established by infecting the corneas of BALB/c mice with F. solani. The cutinase antibody specifically detected Fusarium antigens in the tear-wash samples and eyeball lysates of FK mice. These results demonstrate that the cutinase antibody is highly specific to F. solani antigens, indicating its potential utility in developing an antibody-based diagnostic method for FK.